Biomass Prediction in Leucaena leucocephala - Khan, T. A.; Pathak, P. S. (Indian Forester, 1994)
Study has been carried out on prediction of biomass in Leucaena leucocephala (Lam.) de wit, Data pertaining to biomass/growth attributes on one hundred plants ranging from 3.5 to 7.5 year growth have been taken by actua1 felling of trees. Optimum prediction equations were decided on the basis of Coefficient of determination (r3) along with significance of regression with its minimum standard error. It has obtained from the data presented, that variation in the biomass/growth had increasing trend upto 6.5 year and decline afterwards. It was found that dbh provides the optimum prediction of biomass with good precision. Biomass prediction table, according to different dbh growth was also computed.